PROPERTIES OF FRACTURED-POROUS COLLECTORS FROM PM VSP AND LOGGING DATA - Meged G.; Sorokin A. (My University, 2001)
Capabilities of the polarisation method vertical sesmic profiliring – PM VSP and logging to prediction collectors properties of geological section in near borehole space are considered. Fractured-porous collectors with different composition fluids saturation (gas, oil, condensate, water, hydrate, or mixtures theirs fluids), with dispersional shaliness – it is real picture of hydrocarbon traps. The anisotropy of permeability of a section is connected to a direction of opens fractures. The opening and direction of fractures is instituted by a composite tension of environment containing of fractured-porous collectors. During propogation of seismic waves in environment of such type takes place composite dynamic processes of dissipation of energy in all directions, which are mirrored in changes of poiarisation, dynamical and kinematical parameters both shear and compressional waves [1]. Most reliable information about a constitution and character of fluid saturation in near borehole space a part of hunders meters from a well can be received under data of the technological complex polarisation method of vertical seismic profiliring – PM VSP, logging and results of petrophysical core testing.